Development of quality management systems for support services in the South African public higher education institutions - Makola, A.M.; Ramchander, M.; Naidoo, R. (South African Journal of Higher Education, 2025)
Quality management in higher education has become an area of focus receiving attention both at national and at institutional levels. While the academic enterprise is subject to accreditation and reviews of its academic programmes, by contrast, the support services sector is not subjected to any mandatory reviews and self-assessment processes. Thus, the aim of this study was to explore the extent to which quality management systems have been adopted by South African public higher education institutions’ (SAPHEIs’) support services, by examining the current practices of implementation. Interviews were conducted with quality directors and managers, support service sector unit heads, as well as senior academics from six purposefully selected SAPHEIS’s. The findings highlight the variance in the SAPHEIs’ development implementation of internal quality management systems as well as the absence of systematic approaches to the quality management of the support services sector. The study argues for the conceptualisation and operationalisation of quality management systems in the support services sector. The recommendations that emanate from the study include the need to: build an institution-wide culture of quality and continuous improvement; develop a systematic approach to quality management that is grounded on well-designed systems thinking approach support sector service quality models, policies and procedure guidelines; and develop tools and processes for assessing quality of support services, feedback mechanisms and self-assessment systems.